Influence of Different Chromatographic Conditions on the Level of Detection and Quantitation of Spironolactone by means of TLC-Densitometry - Małgorzata Dołowy (Journal of Analytical Methods in Chemistry)
The aim of this study was to estimate the influence of different chromatographic conditions on the limits of detection and limits of quantitation (LODs and LOQs) of spironolactone by means of TLC-densitometry under different chromatographic conditions. A comparison of results obtained showed that the choice of appropriate chromatographic conditions for NP-TLC and RP-TLC analysis with densitometry could effectively decrease the LODs and LOQs of spironolactone. Of all chromatographic systems tested, the best was the one comprising chromatographic plates precoated with a mixture of silica gel 60, kieselguhr F254, and mobile phase A (n-hexane-ethyl acetate-glacial acetic acid, 24.5 : 24.5 : 1, v/v/v). The estimated average LOD and LOQ values were 0.034 and 0.103 μg/spot, respectively. This indicates that the described procedure is sufficiently sensitive for the identification and quantification of spironolactone alone. Thereby, the simple and cost-effective TLC-densitometric method can be utilized for the routine quality control of spironolactone in bulk drugs as well as in simple pharmaceutical formulations.